Feasibility Analysis of Patin Fish (Pangasionodon hyphoptalamus) Nursery Business in Sukamandijaya Village, Ciasem District Subang Regency - Nunik Nurfitri Martono; Abubakar; Muhamad Rom Ali Fikri (Grouper, 2024)
Fish breeding is one of the businesses that many fisheries farmers are involved in Sukamandijaya Village is one of the areas producing freshwater fish seeds, especially patin fish (pangasius fish). The production process of patin fish nurseries takes 4-5 weeks. Farmers will receive their income if all patin breeds are sold. There are several obstacles for patin fish nursery farmers related to capital, which still uses personal funds that hamper the next production process. Patin nursery farmers who have narrow marketing will need more time so that all fish breeds are sold, thus hampering farmers' income. This study aims to analyze the average costs required, revenue, income feasibility, and related evaluation of the patin fish breeding business in Sukamandijaya Village. The number of respondents in this study was 28 respondent farmers in Sukamandijaya Village. The analysis used in this study is the calculation of farm income, R / C Ratio, price BEP, production BEP, and revenue BEP. The results showed that the patin fish breeding farm in Sukamandijaya Village had fulfilled the feasibility criteria. The average variable cost required in one production is Rp 4.477.357, and the average fixed cost required in one production is Rp 1.636.801. The average total cost for Rp 6.109.417/production with total revenue obtained of Rp 13.178.610/ production and total income of Rp 7.069.193/production. Analysis of business feasibility obtained an R/C Ratio value of 2,15. Price BEP was obtained at Rp 41.72/head/production, production BEP of 27.542 heads/production, and revenue BEP of Rp Rp 2.472.818,18/production.